Upaya Meningkatkan Gerak Dasar Lokomotor pada Siswa Kelas 3 di SDN Pakis 8 dengan Permainan Tradisional Gobak Sodor - Ahkmat Yusuf Hariyanto; Vega Chandra Dinata; Retno Mundi Pertiwi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to improve the basic locomotor motor skills of grade 3B students of SDN 8 Surabaya through learning based on the traditional game Gobak Sodor. This study uses the Classroom Action Research (PTK) method which consists of two cycles, with the stages of planning, action, observation, and reflection. Data collection techniques are carried out through observation and documentation. The results of the study showed a significant improvement in the basic locomotor movement ability of students, such as running, jumping, and jumping. In the pre-cycle, the average student score was 51.48 with classical completeness of 40%. After the implementation of the Gobak Sodor game, there was an increase in the first cycle with an average score of 60.2 and classical completeness of 60%, and in the second cycle with an average score of 75.92 and classical completeness of 80%. The game of Gobak Sodor has proven to be effective in developing students' gross motor skills and increasing their motivation. Although the overall results show significant progress, some students still need more attention to achieve optimal results.